The Dynamic Impact of Exporting on Firm R&D Investment - Florín G. Maican; Matilda Orth; Mark J. Roberts; Van Anh Vuong (Research Institute of Industrial Economics (IFN), 2020)
Economic theory predicts that outsourcing public services to private firms will reduce costs, but the effect on quality is ambiguous. We explore quality differences between publicly and privately owned ambulances in a setting where patients are as good as randomly assigned to ambulances of different ownership statuses. We find that privately owned ambulances are better at responding to contracted quality measures but perform worse on noncontracted measures, such as mortality. In fact, a randomly allocated patient has a significantly higher risk of death if a private ambulance is dispatched. We also present suggestive evidence on the mechanism, supporting that private firms cost innovate at the expense of ambulance staff quality.
Keywords: F13; L60; L13; O30; 330; R&D; Innovation; Trade policy; Productivity